2010
DOI: 10.1111/j.1467-9485.2010.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Uk/Us Exchange Rate With Divisia Monetary Models and Neural Networks

Abstract: This paper compares the UK/US exchange rate forecasting performance of linear and nonlinear models based on monetary fundamentals, to a random walk (RW) model. Structural breaks are identified and taken into account. The exchange rate forecasting framework is also used for assessing the relative merits of the official Simple Sum and the weighted Divisia measures of money. Overall, there are four main findings. First, the majority of the models with fundamentals are able to beat the RW model in forecasting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Bissoondeeal et al (2011) stressed that the most accurate forecasts of the UK/U,S. Bissoondeeal et al (2011) stressed that the most accurate forecasts of the UK/U,S.…”
Section: Literature Review On Exchange Rate Forecastingmentioning
confidence: 99%
“…Bissoondeeal et al (2011) stressed that the most accurate forecasts of the UK/U,S. Bissoondeeal et al (2011) stressed that the most accurate forecasts of the UK/U,S.…”
Section: Literature Review On Exchange Rate Forecastingmentioning
confidence: 99%
“…Following studies such as Bissoondeeal et al . (), we use the Treasury bill rate (TBR), a short term rate, as the opportunity cost variable. Data on consumer price index (CPI), GDP, TBR and ULC are obtained from Datastream.…”
Section: Datamentioning
confidence: 99%
“…Household sector Simple Sum and Divisia aggregates, for the M4 level of aggregation, were obtained from the Bank of England's website. 8 Following studies such as Bissoondeeal et al (2011), we use the Treasury bill rate (TBR), a short term rate, as the opportunity cost variable. Data on consumer price index (CPI), GDP, TBR and ULC are obtained from Datastream.…”
Section: Data and Preliminary Analysismentioning
confidence: 99%
“…The RMB forecasting from BPNN is precise and efficient. Bissoondeeal et al (2011) compared UK/US exchange rate forecasting performance of linear and nonlinear models based on monetary fundamentals, to a RW model. They concluded that the most accurate forecasts of the UK/US exchange rate are obtained with a nonlinear model.…”
Section: Introductionmentioning
confidence: 99%